Gallic Acid Attenuates Cisplatin-Induced Apoptosis, Oxidative Stress, and Inflammation in Cardiomyocytes - Yazğan, Betül; Yazğan, Yener (Online Turk Saglik Bilimleri Dergisi, 2024)
Objective: Cisplatin (CIS) is a powerful chemotherapeutic agent that has long been used alone or in combination in the treatment of various cancers. However, the toxicity of CIS in various tissues limits its use. Gallic acid (GAL) has anti-microbial, anti-inflammatory, and anti-tumor properties. Since GAL has broad biological properties and exhibits antioxidant activity, this study aimed to investigate the effect of GAL on CIS-induced cardiotoxicity in H9c2 cardiomyocyte cell lines. Materials and Methods: H9c2 cardiomyocyte cells as control (CON), CIS, and GAL25, GAL50 in combination along with CIS were used. In the analyses made, glutathione (GSH) and glutathione peroxidase (GSH-Px) enzyme activity, lipid peroxidation levels, inflammation markers IL1β, IL 6, and TNF α, Total Oxidant/ Antioxidant (TOS and TAS) status, reactive oxygen species (ROS) and caspase (Casp 3-9) activity in the cells were determined. Results: CIS treatment caused cardiomyocyte cell toxicity and increased Casp 3-9, ROS, IL 1β, TNF α, IL 6, TOS, and MDA levels while decreasing GSH-Px, GSH, and TAS levels. Increased inflammation and impaired oxidant/antioxidant balance in cardiomyocyte cells after CIS treatment were regulated by GAL treatment. Conclusions: GAL treatment was found to have a protective effect on CIS-induced cardiotoxicity in cardiomyocyte cells.
Keywords: Cell Physiology; Gallik asit; H9c2 kardiyomiyosit; kardiyotoksisite; oksidatif stres; sisplatin; Cardiotoxicity; cisplatin; gallic acid; H9c2 cardiomyocyte; oxidative stress; Hücre Fizyolojisi